2000
DOI: 10.2337/diacare.23.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral hypoglycemic agents and diet on protein metabolism in type 2 diabetes.

Abstract: 1T he roles of insulin deficiency and t reatment in protein homeostasis are well documented in type 1 diabetes (1-8) but insulin' s role in type 2 diabetes remains uncertain. The American Diabetes Association recently concluded that t h e re were insufficient data on which to make firm dietary protein re c o m m e n d ations (9), and one expert renewed the call for more re s e a rch (10). We have re p o rt e d that protein metabolism is accelerated in moderately hyperglycemic obese diabetic subjects when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(33 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23]. Our results suggest this effect may occur independently of protein intake although a higher protein intake has previously been shown to suppress proteolysis of lean tissue in obese healthy adults [24].…”
Section: Discussionmentioning
confidence: 58%
“…This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23]. Our results suggest this effect may occur independently of protein intake although a higher protein intake has previously been shown to suppress proteolysis of lean tissue in obese healthy adults [24].…”
Section: Discussionmentioning
confidence: 58%
“…We predict that the insulinresistant subjects of these previous studies would have had insulin resistance of protein metabolism, and that treatment with rosiglitazone [5] or metformin [48] would have decreased that resistance, contributing to the decreased plasma ADMA with treatment. We have shown that a hyperglycaemia-associated increase in protein turnover could be normalised during euglycaemia with diet, metformin and sulfonylurea treatment [10]. In this regard, it is noteworthy that decreased aortic DDAH activity correlates positively with elevated plasma ADMA in streptozotocininduced diabetes in rats [49].…”
Section: Discussionmentioning
confidence: 86%
“…Assays for immunoreactive insulin and glucagon, and glucose-specific activity are described in [10,20]. Plasma total BCAA were measured by a rapid enzymatic, fluorometric assay [16] during the clamp.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in healthy individuals and in individuals with type 2 diabetes have demonstrated that glucose produced from ingested protein does not increase plasma glucose concentration but does produce increases in serum insulin responses (1,66). Abnormalities in protein metabolism may be caused by insulin deficiency and insulin resistance; however, these are usually corrected with good blood glucose control (67).…”
Section: Position Statementmentioning
confidence: 99%